Tendencia de los sistemas económicos en Sudamérica (1990-2017). - Santana Buele, Aida Veronica (My University, 2018)
The trend of economic systems in South America, have shown the growth and decline in the economy of the countries that make up the region, since 1990 the economies have been facing global economic crises with socialist and capitalist ideologies according to the system with which they are managed to the present. The methodology used for the analysis of this research is descriptive, analytical and bibliographic. With what is intended to analyze the economic situation of South American countries throughout this period (1990-2017), describe the advantages and disadvantages that have caused the different economic systems, synthesize the growth and economic decline of the different countries and An attempt will be made to examine the concrete situation of Chile. It is concluded that in South America two economic systems are used; socialist and capitalist, the same ones that have marked significant features in the economy, the cases that stand out are the one of Venezuela with socialist economy that in recent years has been going through a setback and the case of Chile that despite the political instability of recent years, it is considered one of the economies of the region that maintains its level of growth.
La tendencia de los sistemas económicos en Sudamérica, han mostrado el crecimiento y el retroceso en la economía de los países que conforman la región, desde 1990 estos estados han venido enfrentando crisis económicas mundiales mediante ideologías socialistas y capitalistas acorde al sistema con el que se manejan hasta la actualidad. La metodología utilizada para el análisis de esta investigación es descriptiva, analítica y bibliográfica. Con lo que se pretenderá analizar la situación económica de los países sudamericanos a lo largo de este periodo (1990-2017), describir las características ventajas y desventajas que han ocasionado los diferentes sistemas económicos, sintetizar el crecimiento y retroceso económico de los diferentes países y se procurará examinar la situación concreta de Chile. Se concluye que en América del Sur se utiliza dos sistemas económicos; socialista y capitalista, los mismo que han marcado rasgos significativos en la economía, los casos que resaltan son el de Venezuela con económica socialista que en los últimos años ha venido pasando por un retroceso y el caso Chile que a pesar de la inestabilidad política de los últimos años, se considera como una de las economías de la región que mantiene su nivel de crecimiento.
Keywords: SISTEMAS ECONÓMICOS; CAPITALISMO; SOCIALISMO; CRECIMIENTO; RECESIÓN; ESTABILIDAD; ECONOMÍA